Risk-based contaminant management: Ranger Mine case study - Iles, M; Rissik, D (Mine Closure 2022: 15th International Conference on Mine Closure, 2022)
The Ranger Mine, operated by Energy Resources of Australia Ltd (ERA), is in a sensitive area in Australia’s Northern Territory. It is surrounded by (but separate from) Kakadu National Park (KNP) World Heritage Place and Ramsar wetland. Closure requirements include protecting the KNP values and health of the local people. Impacts from water and tailings contaminants must be as low as reasonably achievable and cause no detrimental impact to the biodiversity or ecological processes of the region. The Indigenous landowners, the Mirarr people, wish to resume cultural activities, including sourcing food, at the site after closure. A source-pathway-receptors approach and a deep dive into environmental exposures and consequences were used to assess the risks from multiple contaminant sources and water pathways for up to 10,000 years after closure. The most hazardous contaminants were identified by comparing measured and modelled water and sediment concentrations against multiple guidelines for human health and ecosystem endpoints reflecting the regulatory environmental requirements for closure and the aspirations of ERA and its stakeholders. Prioritised actions were identified to manage contaminant sources, including a review of key modelling assumptions influencing outcomes, targets for process water treatment and decommissioning plans for plumes and contaminated soils around the tailings storage facility. The assessment used evidence from monitoring, ecological response studies and modelling. Risk descriptors were developed to match the evidence types and frequencies at which guideline values might be exceeded, giving a deep insight into impacts. This case study shows how to modify standard risk assessment tools to match different types of evidence, including probabilistic outcomes solute transport models. The water quality discussed in this report is not that expected after closure. The process discussed here has driven actions to improve water quality on, and downstream of, Ranger Mine after closure. The process can be applied iteratively to revise contaminant management plans thus improving water quality following closure.
Keywords: risk assessment; ecological vulnerability; as low as reasonably achievable (ALARA); closure criteria